Assessment of mandibular ramus thickness in Afro-Brazilian subjects using computed tomography - Costa, Paula Bonfim Almeida; Bittencourt, Marcos Alan Vieira; Rocha Rebello, Iêda Margarida Crusoé (European Journal of General Dentistry, 2014)
Purpose: The purpose of this study was to investigate whether the skeletal pattern in the anteroposterior and vertical directions influences mandibular ramus thickness in Afro-Brazilian subjects, using computed tomography (CT). Materials and Methods: CT images of 45 individuals of Afro-Brazilian, from both genders, aged ranges between 19 and 46 years, were used. Determination of the skeletal pattern in the anteroposterior direction was based on the association of the ANB and WITS values, and in the vertical direction, through the GoGn-SN angle. Measurement of the mandibular ramus was performed just above the lingula in the coronal plane after three-dimensional reconstruction of the image and multiplanar analysis. Results: Twenty-seven of the 45 images were from individuals with Class I skeletal pattern, 13 Class II and 5 Class III, with means of 7.19 mm, 7.15 mm and 7.3 mm, respectively (P = 0.95). In the vertical direction, 4 individuals exhibited reduced vertical skeletal pattern, 28 normal pattern and 13 increased pattern, with means of 7.01 mm, 7.15 mm and 7.33 mm, respectively (P = 0.77). Conclusion: No statistically significant difference was found in mandibular ramus thickness in the different skeletal patterns, both in the anteroposterior and vertical directions.
Keywords: African Continental Ancestry Group; mandible; osteotomy; sagittal split ramus; tomography; X-ray